Chapter «La forza del naturale tradotta dallo spagnolo»: su un'ignota riscrittura italiana de La fuerza del natural di Agustín Moreto e Jerónimo de Cáncer a Vienna - Usula, Nicola (Studi e saggi, 2020)
Among the manuscripts in Italian kept in the National Library of Vienna, a comedy in prose of Spanish derivation has recently come to light, hitherto neglected by theatrological and Hispanistic studies. The title page of the booklet declares at the beginning the nature of the content with a laconic "La forza del naturale translated from Spanish », which identifies the text as a translation and revision of La fuerza del natural by Agustín Moreto and Jerónimo de Cáncer (perhaps with the collaboration of Juan de Matos Fragoso), probably composed between 1644 and 1654 and printed for the first time in 1661. Where and when was written the text passed down by the Viennese witness? Was it imported from Italy or written beyond the Alps? Finally, is it possible to trace the exact hypotext starting from the twenty sources known today of the Spanish comedy? This study answers these questions and sheds light on the adaptation techniques that emerged from the comparison between the Italian text and its Spanish hypotext, also by taking into account the elements relating to music distributed throughout the comedy: dances, singing and musical instruments on stage.